MIGRASI PERLUASAN FRONTIER PEMUKIMAN, DAN PERUBAHAN DEMOGRAFIS: KARESIDENAN BESUKI, 1870-1970 - nfn Nawiyanto (Balai Arkeologi Kalimantan Selatan, 2009)
In a hundred years since 1870, the population grew rapidly in Karesidenan Besuki due to powerful migration flow. The arrival of migrants from Madura and Java wasÂ complemented by settlement frontier expansion from north southward and from west eastward. The once natural environment m the mtenor of Besuki had gradually vanished and became man made environment. Apparently, the migration also changed its demographtc patterns whtch was mdtcated by the concentration of population in a number of places, specifically, Jember; its population growth was over the density rate in northern coast of Java and made it the third biggest city in East Java. Hence, Besuki became a multicultural cityÂ occupied by three dominant social groups i.e. Madura, Java and Osing. ThisÂ article discusses the phases of frontier extended at Karesidenan Besuki and the influences of migration to demoghraphy pattern at this area.